The Impact of the Implementation of Good Governance Principles and Internal Audit Functions on Fraud in the Management of BOS Funds In Bengkulu City - Sari, Puti Mayang; Marietza, Fenny; Aprila, Nila (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2026)
This study aims to provide empirical evidence of the influence of the implementation of good governance principles and internal audit function on fraud in the management of BOS (School Operational Assistance) funds in Bengkulu City. This research is classified as descriptive quantitative research. Data were collected through online questionnaires distributed to respondents. The research respondents consisted of BOS fund managers in elementary and junior high schools, including school principals of BOSP treasurers. The sample was selected using a simple random sampling technique, with a total of 168 respondents. The analytical methods used include descriptive analysis and regression analysis. The results show that the implementation of good governance principles and internal audit has a significant negative effect on fraud in the management of BOS funds in Bengkulu City. This indicates that the application of good governance principles and the effective implementation of internal audit functions can narrow the space for irregularities to occur and serve as mechanisms for early detection and prevention of misuse and mismanagement of BOS funds.